Analisis Kualitas Pelayanan Antenatal Care dengan Kepuasan Ibu Hamil di Puskesmas Pematang Kandis Kabupaten Merangin - Ulina, Marta; Djago, Y. Ony; Rulia, Rulia; Nugroho, Taufan; Yuliaty, Farida (Jurnal Akademika Baiturrahim Jambi, 2026)
Antenatal care (ANC) services play an important role in maintaining maternal and fetal health. However, the quality of services in primary healthcare facilities is still not optimal, and dissatisfaction among pregnant women has been identified, particularly in aspects of communication, empathy, and waiting time. Data from the Kementerian Kesehatan Republik Indonesia indicate that ANC visit coverage has not yet reached the expected targets over the past three years (Ministry of Health, 2022–2024). A preliminary study conducted at Puskesmas Pematang Kandis, Merangin Regency, also revealed complaints from pregnant women regarding inadequate information and limited attention from healthcare providers.This study aims to analyze the relationship between the quality of antenatal care services and the satisfaction of pregnant women at Puskesmas Pematang Kandis, Merangin Regency, in 2024. This study employed a quantitative analytical design with a cross-sectional approach. The population consisted of 328 pregnant women, with a sample of 77 respondents selected using purposive sampling, based on inclusion criteria of pregnant women who attended ANC visits and were willing to participate. Data were analyzed using univariate and bivariate analysis (Chi-Square test). The results showed a significant relationship between service quality dimensions, including tangibles (p=0.016), responsiveness (p=0.001), reliability (p=0.031), empathy (p=0.005), and assurance (p=0.003), and the satisfaction of pregnant women. In conclusion, the quality of antenatal care services is significantly associated with the satisfaction of pregnant women. It is recommended that Puskesmas Pematang Kandis improve service quality through effective communication training, enhancement of healthcare providers’ empathy, and improvement of service systems to reduce waiting time